Genome sequencing and characterization of an extensively drug‐resistant sequence type 111 serotype O12 hospital outbreak strain of Pseudomonas aeruginosa. (8th February 2014) - Witney, A. A.; Gould, K. A.; Pope, C. F.; Bolt, F.; Stoker, N. G.; Cubbon, M. D.; Bradley, C. R.; Fraise, A.; Breathnach, A. S.; Butcher, P. D.; Planche, T. D.; Hinds, J.; et al.
Abstract A series of extensively drug‐resistant isolates of Pseudomonas aeruginosa from two outbreaks in UK hospitals were characterized by whole genome sequencing (WGS). Although these isolates were resistant to antibiotics other than colistin, we confirmed that they are still sensitive to disinfectants. The sequencing confirmed that isolates in the larger outbreak were serotype O12, and also revealed that they belonged to sequence type ST111, which is a major epidemic strain of P. aeruginosa throughout Europe. As this is the first reported sequence of an ST111 strain, the genome was examined in depth, focusing particularly on antibiotic resistance and potential virulence genes, and on the reported regions of genome plasticity. High degrees of sequence similarity were discovered between outbreak isolates collected from recently infected patients, isolates from sinks, an isolate from the sewer, and a historical isolate, suggesting that the ST111 strain has been endemic in the hospital for many years. The ability to translate easily from outbreak investigation to detailed genome biology by use of the same data demonstrates the flexibility of WGS application in a clinical setting.